Information Technology in Bio- and Medical Informatics Second International Conference, ITBAM 2011, Toulouse, France, August 31 - September 1, 2011, Proceedings - Böhm, Christian; Khuri, Sami.; Lhotská, Lenka; Pisanti, Nadia; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2011)
This book constitutes the thorougly refereed proceedings of the Second International Conference on Information Technology in Bio- and Medical Informatics, ITBAM 2011, held in Toulouse, France, in August/September 2011, in conjunction with DEXA 2011. The 13 long papers and 5 short papers were carefully selected and address the following topics: decision support and data management in biomedicine; medical data mining and information retrieval; workflow management and decision support in medicine; and classification in bioinformatics. The papers show how broad the spectrum of topics in applications of information technology to biomedical engineering and medical informatics is.
Keywords: Information storage and retrieval; Data mining; Database management; Application software; Bioinformatics; Information Storage and Retrieval; Data Mining and Knowledge Discovery; Database Management; Information Systems Applications (incl. Internet).; Computational Biology/Bioinformatics.